Mental health disorders and chronic opioid use among adolescents and young adults with chronic pain - Richardson, Laura P. (2012)
BACKGROUND: The purpose of this study was to examine the association between mental health disorders and subsequent risk for chronic opioid use among adolescents and young adults presenting with common chronic pain complaints (back pain, neck pain, headache and arthritis/joint pain). METHODS: Using claims data from January 1, 2001 to June 30, 2008, we conducted a longitudinal analysis of opioid use patterns among 13–24 year-olds presenting with a new episode of chronic pain. Chronic opioid use was defined as receiving >90 days of opioids within a 6-month period with no gap in use of >30 days in the 18 months following the fist qualifying pain diagnosis. Mental health disorders were identified from claims in the 6 months prior to the first qualifying pain diagnosis. RESULTS: 59,077 youth met criteria for a new episode of chronic pain. Among these youth, 321 (0.5%) met criteria for chronic opioid use and 16,172 (27.4%) had some opioid use. After controlling for demographic and clinical factors, youth with pre-existing mental health diagnoses had a 2.4-fold increased risk of subsequently receiving chronic opioids versus no opioids (OR: 2.36, 95% CI = 1.73–3.23) and a 1.8-fold increased likelihood of receiving chronic opioids versus some opioids (OR: 1.83, 95% CI= 1.34–2.50). CONCLUSIONS: Mental health disorders are associated with increased risk for chronic opioid use among adolescents and emerging young adults. Further study is warranted to examine risks and benefits of chronic opioid use in this population.